Financial structure and its impact on the convergence of interest rate pass-through in Europe: A time-varying interest rate pass-through model - Wolfgang Schwarzbauer (Institute for Advanced Studies (IHS), 2006)
So far studies concerned with the interest pass-through of monetary policy have not taken into account one central issue that arose in Europe in the late 1990s: the importance of financial structure for the convergence of monetary transmission. This study addresses this shortcoming. We estimate a time varying interest pass-through allowing us to test for the importance of financial structure and its impact on the convergence of the effects of monetary policy. We find convergence in banks' reaction to money market movements, which is additionally reduced in groups of countries with similar financial structure. Furthermore, there is a significant impact of financial structure on the extent of transmission of monetary policy impulses within the same month. Thus, differences in financial structure between countries must not be ignored when considering convergence of monetary transmission in Europe.
Keywords: E43; G21; E52; 330; convergence; interest rate pass-through; EMU; financial structure; money and bank interest rates; transmission mechanism; Öffentliche Finanzwirtschaft; Geldpolitik; Zinspolitik; Europa